Ufl1 deficiency causes skin pigmentation by up-regulation of Endothelin-1 - Wang, Ke; Xu, Hu-Ning; Wang, Yi-Wen; Mao, Jian; Liu, Da; Zhu, Xiao-Jing; Cong, Yu-Sheng; Wang, Miao (Frontiers in Cell and Developmental Biology, 2022)
Ufmylation (UFM1 modification) is a newly identified ubiquitin-like modification system involved in numerous cellular processes. However, the regulatory mechanisms and biological functions of this modification remain mostly unknown. We have recently reported that Ufmylation family genes have frequent somatic copy number alterations in human cancer including melanoma, suggesting involvement of Ufmylation in skin function and disease. UFL1 is the only known Ufmylation E3-like ligase. In this study, we generated the skin-specific Ufl1 knockout mice and show that ablation of Ufl1 caused epidermal thickening, pigmentation and shortened life span. RNA-Seq analysis indicated that Ufl1 deletion resulted in upregulation of the genes involved in melanin biosynthesis. Mechanistically, we found that Endothelin-1 (ET-1) is a novel substrate of Ufmylation and this modification regulates ET-1 stability, and thereby deletion of Ufl1 upregulates the expression and secretion of ET-1, which in turn results in up-regulation of genes in melanin biosynthesis and skin pigmentation. Our findings establish the role of Ufl1 in skin pigmentation through Ufmylation modification of ET-1 and provide opportunities for therapeutic intervention of skin diseases.